Mindsets shape consumer behavior - Murphy, Mary C.; Dweck, Carol S. (Journal of Consumer Psychology, 2016)
Abstract Mindsets—or implicit theories—are the beliefs people have about the nature of human characteristics. This article applies mindset theory and research to the field of consumer behavior. Specifically, we suggest how a fixed or growth mindset may shape consumer product preferences, acceptance of brand extensions, trust recovery following product failures, as well as the effectiveness of advertising and marketing campaigns. We argue that people with a fixed mindset are more likely to seek products and brands in line with their goals to burnish their self‐image and demonstrate their positive qualities, while people with a growth mindset seek products that help them pursue their goals to improve and learn new things. Thus, products and brands may serve important self‐enhancement functions—encouraging consumers to reinforce or expand core aspects of their identity. We also suggest that brands and companies can project a fixed or growth mindset. In turn, these organizational mindsets should shape consumers' expectations of, and relationships with, products, brands, and companies.